(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
: Social media has become an inseparable part of the daily lives of young people worldwide. This paper examines both the positive and negative impacts of social media on youth, focusing on education, lifestyle, and psychological well-being. The study is based on a literature review of international research articles, statistical reports, and local sources from Uzbekistan. Findings show that while social media enhances access to information, global communication, and self expression, it also poses risks such as addiction, exposure to misinformation, and mental health challenges. The paper argues that balanced and responsible use of social media can maximize its benefits while minimizing potential harms. Recommendations are provided for educators, parents, and policymakers to promote digital literacy and encourage safe online practices among youth.